An Optogenetic Method to Study Signal Transduction in Intestinal Stem Cell Homeostasis. Issue 10 (1st May 2020) - Bunnag, Nawat; Tan, Qian Hui; Kaur, Prameet; Ramamoorthy, Anupriya; Sung, Isabelle Chiao Han; Lusk, Jay; Tolwinski, Nicholas S.
Abstract: Homeostasis in adult organs involves replacement of cells from a stem cell pool maintained in specialized niches regulated by extracellular signals. This cell-to-cell communication employs signal transduction pathways allowing cells to respond with a variety of behaviors. To study these cellular behaviors, signaling must be perturbed within tissues in precise patterns, a technique recently made possible by the development of optogenetic tools. We developed tools to study signal transduction in vivo in an adult fly midgut stem cell model where signaling was regulated by the application of light. Activation was achieved by clustering of membrane receptors EGFR and Toll, while inactivation was achieved by clustering the downstream activators ERK/Rolled and NFκB/Dorsal in the cytoplasm, preventing nuclear translocation and transcriptional activation. We show that both pathways contribute to stem and transit amplifying cell numbers and affect the lifespan of adult flies. We further present new approaches to overcome overexpression phenotypes and novel methods for the integration of optogenetics into the already-established genetic toolkit of Drosophila . Graphical abstract: Unlabelled Image Highlights: Maintenance of tissue homeostasis requires the regulation of somatic stem cells. A simple, genetically tractable model for stem cell behaviour is the Drosophila gut allowing studies of stem cell maintenance and proliferation. In this work, we add optogenetics to this system to regulate signal transduction to observe cell fate decisions. Toll Pathway on/off switches EGFR Pathway on/off switches Endogenous gene optogenetics system through RMCE